Pengaruh Konflik Pekerjaan Keluarga (Work Family Conflict) dan Stres Kerja terhadap Kinerja Karyawan pada PT. Warahma Biki Makmur Kabupaten Tuban (Studi Pada Karyawan Wanita Devisi Gulung) - Eva Lufiana Dina Safitri; Muhammad Alkirom Wildan (Jurnal Kajian Ilmu Manajemen (JKIM), 2021)
This study aims to partially the effect: (1) the influence of work family conflict on the performance of women employees of the roll devision at PT Warahma Biki Makmur (2) the influence of work stress on the performance of women employees at PT Warahma Biki Makmur Tuban Regency. This research includes causal associative research with quantitative approaches. The results showed that: (1) work family conflict positive and significant affects the performance of women employees of the roll devision at PT Warahma Biki Makmur. This is indicated by the value of the regression coefficient (β) of 0.691 and the p value (sig) of 0.000. (2) work stress negative and significant affects the performance of women employees of the roll devision at PT Warahma Biki Makmur. This is indicated by the beta coefficient (β) of -0.462 and the p value (sig) of 0.000.